1998
DOI: 10.1016/s0014-5793(98)00134-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and tissue expression of porcine β‐defensin‐1

Abstract: Beta-defensins constitute an emerging family of cysteine-rich antimicrobial peptides, which are particularly prominent at mucosal epithelial sites in mammals. Here we report the identification of a novel L L-defensin from porcine tissues, porcine L L-defensin-1 (pBD-1). The cDNA sequence of pBD-1 encoded a 64 amino acid prepro-peptide, which contained the L L-defensin consensus sequence of six invariantly spaced cysteine residues. Northern blot analysis showed that pBD-1 was expressed abundantly in tongue epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 19 publications
4
60
0
Order By: Relevance
“…Obviously, this is not the case. The expression of pBD-1 correlates well with the pattern described before (Zhang et al, 1998). For pBD-2 no expression sites have been described, but based on these studies, high levels of pBD-2 mRNA are found in liver, kidney and to a lesser extend aorta.…”
Section: Discussionsupporting
confidence: 83%
“…Obviously, this is not the case. The expression of pBD-1 correlates well with the pattern described before (Zhang et al, 1998). For pBD-2 no expression sites have been described, but based on these studies, high levels of pBD-2 mRNA are found in liver, kidney and to a lesser extend aorta.…”
Section: Discussionsupporting
confidence: 83%
“…A novel AMP, termed NK-lysin, was isolated from porcine small intestine and has been shown to be a new effector molecule of cytotoxic T and NK cells [5]. Recently, a porcine β-defensin, pBD-1 was cloned and found to be expressed throughout epithelia of the respiratory and gastrointestinal tracts [134]. All of these AMPs, except cecropin P1 and NK-lysin, belong to either the defensin or the cathelicidin family, which are the two major groups of AMPs found in most mammalian species [37][38][39]66].…”
Section: Arsenal Of Porcine Ampsmentioning
confidence: 99%
“…Recently, we cloned the full-length cDNA for pBD-1, which is the only member of the defensin family identified in pigs thus far [134]. The pBD-1 mRNA is expressed abundantly in tongue epithelia and to a lesser extent throughout the respiratory and digestive tracts.…”
Section: Pbd-1 a Porcine Form Of Epithelial β-Defensinmentioning
confidence: 99%
“…The only member of the defensin family identified in pigs thus far is the porcine β-defensin [77]. Although α-defensins are the most abundant anti-microbial peptides in granules of polymorphonuclear cells or intestinal Paneth cells in many mammalian species [79], they have not been found in pigs.…”
Section: Role Of Iec In the Secretion Of Defensins And Other Antibactmentioning
confidence: 99%